Human Mass Balance and Metabolite Profiling of [14C]‐Pamiparib, a Poly (ADP‐Ribose) Polymerase Inhibitor, in Patients With Advanced Cancer. Issue 9 (19th April 2021) - Mu, Song; Palmer, Daniel; Fitzgerald, Richard; Andreu‐Vieyra, Claudia; Zhang, Heather; Tang, Zhiyu; Su, Dan; Sahasranaman, Srikumar
Abstract: Pamiparib, a selective poly (ADP‐ribose) polymerase 1/2 inhibitor, demonstrated tolerability and antitumor activity in patients with solid tumors at 60 mg orally twice daily. This phase 1 open‐label study (NCT03991494; BGB‐290‐106) investigated the absorption, metabolism, and excretion (AME) of 60 mg [ 14 C]‐pamiparib in 4 patients with solid tumors. The mass balance in excreta, blood, and plasma radioactivity and plasma pamiparib concentration were determined along with metabolite profiles in plasma, urine, and feces. Unchanged pamiparib accounted for the most plasma radioactivity (67.2% ± 10.2%). Pamiparib was rapidly absorbed with a median time to maximum plasma concentration (Cmax ) of 2.00 hours (range, 1.00‐3.05 hours). After reaching Cmax, pamiparib declined in a biphasic manner, with a geometric mean terminal half‐life (t1/2 ) of 28.7 hours. Mean cumulative [ 14 C]‐pamiparib excretion was 84.7% ± 3.5%. Pamiparib was mainly cleared through metabolism, primarily via N‐oxidation and oxidation of the pyrrolidine ring. A dehydrogenated oxidative product (M3) was the most abundant metabolite in biosamples. A mean of 2.11% and 1.11% of [ 14 C]‐pamiparib was excreted as unchanged pamiparib in feces and urine, respectively, indicating near‐complete absorption and low renal clearance of parent drug. Cytochrome P450 (CYP) phenotyping demonstrated CYP2C8 and CYP3A involvement in pamiparib metabolism. These findings provide an understanding of pamiparib AME mechanisms and potential drug‐drug interaction liability.